Initial approach to a patient presenting with breathlessness in a resource limited centre in the context of the COVID-19 pandemic: standard operating procedure - Pasangha, Elaina Terese Antonette (International Journal Of Community Medicine And Public Health, 2021)
Background: The community health and training centre at Mugalur village is a primary level healthcare centre. Resident medical officers found an increased number of patients presenting in the winter months with complaints of acute breathlessness as a result of exxcerbations of COPD and asthma. Prior management at the centre included testing for COVID-19 as initial management resulting in delayed treatment of other diseases. To ensure proper management in the context of the COVID-19 pandemic an SOP was designed. Methods: A quality improvement project which is a cross sectional analysis using plan-do-study-act cycles was conducted. Response and effectiveness was later recorded qualitatively from the staff and quantitatively by comparing with baseline data from prior records periodically at the end of each cycle. Results: Out of the 87 patients seen in the PDSA1, the mean age was 56.0 (SD=11.052) years. About 59.3% of patients were male. 27.6% patients belonged to lower socioeconomic status. Understanding was seen by 100% and 78% of doctors and healthcare workers during PDSA1 and by 100% by both groups in PDSA2. 84% followed the SOP in PDSA1 and 93% in PDSA2. Everyone followed SOP in PDSA3. Number of hospital admissions was found to significantly reduce to 25.5% from 30% at baseline and during PDSA1 following implementation of the SOP. Conclusions: A standardized guideline based on local epidemiology of the disease not only eases management for praticising physicians but also results in improved patient outcomes. This novel protocol can be used to manage patients presenting with acute onset breathlessness in similar resource limited centres.